Early relapse during B lymphocyte depletion of children with frequently relapse /steroid dependent nephrotic syndrome after rituximab treatment - Juan Tu; Ling Wan; Huarong Li; Chaoying Chen (BMC Nephrology)
Abstract Background Patients with frequent relapsing or steroid-dependent nephrotic syndrome (FRSDNS) often maintain remission during the period of B lymphocyte depletion following rituximab (RTX) administration. However, a subset of patients may experience early relapse and subsequently develop refractory disease. In this retrospective study, we summarized the clinical characteristics and outcomes of patients who experienced early relapse during B lymphocyte depletion. Methods This was a retrospective cohort study. The relapse group included six FRSDNS cases with early relapse during B lymphocyte depletion, while the control group consisted of 15 patients without relapse. A comparative analysis was performed on the clinical characteristics and follow-up outcomes of the two groups. Results Compared with the control group, the relapse group exhibited a higher proportion of elevated CD4 + T cell levels (100% vs. 47%, P = 0.046) and lower doses glucocorticoid administration (83.3% vs. 26.7%, P = 0.046) at baseline. Following RTX injection, patients in the control group maintained remission within six months, and the number of relapses within the first year was higher in the relapse group than in the control group. [1.5 (1, 2.5) vs. 0 (0, 0)], Z= -3.708, P = 0.000)]. Conclusion Early-stage relapses were predominantly observed in patients who received lower doses glucocorticoids or had higher CD4 + lymphocyte levels at baseline. Patients experiencing early relapse demonstrated lower overall efficacy with RTX treatment. Clinical trial number not applicable.